2020
DOI: 10.1161/jaha.120.016595
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Calcified Nodule as a Cause of Early In‐Stent Restenosis in Patients Undergoing Dialysis

Abstract: Background Dialysis is an independent risk factor for in‐stent restenosis (ISR) after stent implantation in coronary arteries. However, the characteristics of ISR in patients undergoing dialysis remain unclear, as there are no histological studies evaluating the causes of this condition. The aim of the present study was to investigate the causes of ISR between patients who are undergoing dialysis and those who are not by evaluating tissues obtained from ISR lesions using directional coronary athere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
4
27
0
Order By: Relevance
“…Like CN in native coronary arteries, the potential mechanisms of instent CN must be discussed. Nakamura et al reported histopathologic analysis of ISR lesions obtained by directional coronary atherectomy from hemodialysis patients and suggested that one of the potential mechanisms of in-stent CN is related to the protrusion of a CN (already present at the time of stenting) into the lumen through the stent struts [4]. In our institution, we have received over 1200 stents from 700 sudden death individuals for over 2 decades [5].…”
mentioning
confidence: 96%
“…Like CN in native coronary arteries, the potential mechanisms of instent CN must be discussed. Nakamura et al reported histopathologic analysis of ISR lesions obtained by directional coronary atherectomy from hemodialysis patients and suggested that one of the potential mechanisms of in-stent CN is related to the protrusion of a CN (already present at the time of stenting) into the lumen through the stent struts [4]. In our institution, we have received over 1200 stents from 700 sudden death individuals for over 2 decades [5].…”
mentioning
confidence: 96%
“…noted that the protrusion of a CN followed by a calcifying fibrin thrombus might cause an early (2-3 months) in-stent CN. 5 In the present patient, the fact that the in-stent CNs were detected only 2 weeks after the initial PCI indicates that the underlying mechanism is as follows: the underlying CNs (the necrotic core calcium fragments) were manifested as a protrusion due to the debulking by the atherectomy devices and mechanical injury by balloon dilatation and stent implantation, and it progressed in the subacute phase. The current case indicates that acute coronary syndrome due to the progression of in-stent CNs can occur even in the subacute phase (only 2 weeks after the initial PCI).…”
Section: Discussionmentioning
confidence: 55%
“…In addition, CNs have been reported to have a poor prognosis even after treatment, and around 78% of instent restenosis at CN lesions was caused by the formation of a protruding mass with acoustic J o u r n a l P r e -p r o o f shadowing rather than neointimal hyperplasia, which indicated that intrusion of the calcified nodule is the cause of in-stent restenosis after stenting a calcified nodule (4). Also, in-stent CNs are one of the mechanisms of in stent restenosis and were reported to be particularly common in dialysis patients (5); however, the mechanism has not been elucidated. Nakamura et al noted that the protrusion of a CN followed by a calcifying fibrin thrombus might cause early (2-3 months) in-stent CN (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ann Palliat Med 2021 | https://dx.doi.org/10.21037/apm-21-1658 lipid-rich plaque was significantly lower in the HD group (0% versus 43%, respectively; P=0.03) (24). The calcified character of ISR in HD patients poses a great challenge in treatment.…”
Section: Discussionmentioning
confidence: 91%